Discursivity and iconicity of new illustrative genres - Tomić, Boban G (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2015)
Modern business conditions in the media market, as well as the development of professional technologies in the field of press, television and online media, are requiring a significant commitment to creative and innovative processes. The formal and content related structure of visual media, especially the press, television and online media, are experiencing dynamic changes and improvements, mainly based on innovations in the fields of computer technology, modelling of sound and images, as well as graphic design. In such circumstances, in addition to improving the form, content and expressive possibilities illustrative of some of the classic genres, such as photos, illustrations, cartoons, graphs or tables, there are new forms of illustrative character. The emergence of infographics, and development of live-diagrams and visual maps are significantly improving visual communication in the media and becoming the actual media content in print, television and online media. This paper describes and analyses the creative processes and technology components contributing to the emergence and development of new illustrative forms, as well as the needs of their use in the current media practice. We point out the potential that new illustrative genres entries have in the process of mass communication, but also in business practices and results of operations of media companies. Using some representative samples and illustrative examples of the development of the genre, we point to the deficiencies and anomalies that contemporary illustrative form can bring to journalists, editors and their audience. The starting point of this paper is the idea that the development of visual forms of communication must not make vulgar simplification of content of media messages, but the messages should be enriched. Journalism must serve the new illustrative genres in order to increase the informational value of media content, but not at the expense of the discursive form and content.
Keywords: illustrative genre; infographic; photograph; discourse; visual communication; collaboration